2001
DOI: 10.1074/jbc.m008885200
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Threat to Nascent Apolipoprotein B

Abstract: We previously showed that ⍀-3 fatty acids reduce secretion of apolipoprotein B (apoB) from cultured hepatocytes by stimulating post-translational degradation. In this report, we now characterize this process, particularly in regard to the two known processes that degrade newly synthesized apoB, endoplasmic reticulum (ER)-associated degradation and re-uptake from the cell surface. First, we found that ⍀-3-induced degradation preferentially reduces the secretion of large, assembled apoBlipoprotein particles, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(74 citation statements)
references
References 78 publications
0
72
2
Order By: Relevance
“…NIS, nonimmune serum. quality control mechanism, it was demonstrated that apoB can be targeted for degradation at different stages of its maturation beyond the ER (15,40,55,68,69). This, however, is an unlikely scenario occurring in HepG2 cells under the conditions used in this study, because the cells were incubated under conditions that support optimal folding of apoB resulting in a very efficient secretion.…”
Section: Fig 5 Molecular Chaperones Co-immunoprecipitate With Apob mentioning
confidence: 79%
“…NIS, nonimmune serum. quality control mechanism, it was demonstrated that apoB can be targeted for degradation at different stages of its maturation beyond the ER (15,40,55,68,69). This, however, is an unlikely scenario occurring in HepG2 cells under the conditions used in this study, because the cells were incubated under conditions that support optimal folding of apoB resulting in a very efficient secretion.…”
Section: Fig 5 Molecular Chaperones Co-immunoprecipitate With Apob mentioning
confidence: 79%
“…The radioactivity recovered in the four lipid classes associated with each purified apoB-containing lipoprotein was used to calculate the percent radiolabeled lipid composition (Table I). assembly process. Hence, in the absence of MTP, forms of apoB containing a sufficient length of the ␤ 1 domain may undergo aggregation and/or non-native interactions with intracellular membranes, ultimately resulting in intracellular retention and turnover (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of MTP, apoB fails to acquire lipid during translation, causing misfolding and intracellular retention and degradation (25,26). In contrast, coexpression of apoB with MTP promotes nascent lipoprotein formation, which stabilizes apoB and promotes anterograde transport and secretion (23,27).…”
Section: Discussionmentioning
confidence: 99%